Pendampingan Pembuatan Biopori dalam Meningkatkan Kualitas Tanah dan Air di Desa Musir Kidul - Fawwaz Al Adli M; Rosyidatuzzahro Anisykurlillah (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to increase public awareness about the environment by utilizing biopores in Musir Kidul Village. They gather, gain knowledge, and use biopore infiltration holes. As shown by the results of this activity, the community has become more involved and more aware of the importance of protecting the environment. Biopores utilize organic waste and reduce waterlogging.